Correlations among algometry, the visual analogue scale, and the numeric rating scale to assess chronic pelvic pain in women - Mariane M. Alfonsin; Rita Chapon; Carlos A.B. de Souza; Vanessa K. Genro; Marília M.C. Mattia; João S. Cunha-Filho (Elsevier, 2019)
Objective: To investigate the correlation between the numerical rating scale, visual analogue scale, and pressure threshold by algometry in women with chronic pelvic pain. Study design: This was a cross-sectional study. We included 47 patients with chronic pelvic pain. All subjects underwent a pain assessment that used three different methods and were divided according to the cause of pain (endometriosis versus non-endometriosis). Moreover, we assessed the agreement between the scales (visual, analogue and algometry) using the intraclass correlation coefficient (ICC). Results: The ICC for the numeric rating scale and the visual analogue scale regarding pain (0.992), dysmenorrhea (1.00) and dyspareunia (0.996) were strong. The agreement between the scales was excellent (p ≤0.01). The correlation between algometry and the scales showed a moderate and inverse association, and this correlation was statistically significant: as the scores on the numeric rating scale and the visual analogue scale regarding dyspareunia increased, the algometry thresholds decreased. Conclusions: The assessment of women with chronic pelvic pain should combine pressure algometry and the numeric rating scale or the visual analogue scale, because of their inverse correlations and satisfactory reliability and sensitivity, to make pain assessment less subjective and more accurate. Keywords: Chronic pelvic pain, Numeric rating scale, Visual analogue scale, Pressure algometry, Pain in endometriosis